Da Barcellona a Marsiglia. Le politiche dell’Unione europea nel Mediterraneo - Isoni, Alessandro (Rivista di studi politici internazionali, 2022)
The paper analyzes the history of European cooperation in the Mediterranean Sea. Starting from the Cold War period and from the decolonization process, the Author tries to reconstruct the political premises and the interventions implemented by the European Economic Community, analyzing the limits of a similar Eurocentric approach. After the Berlin Wall fall and the Maastricht Treaty, new opportunities offered by the enlargement towards East suggested the European Union to start a Euro-Mediterranean Partnership with North Africa and the Middle East States, in order not to lose a strategic area for the European security. The Barcelona Process, inaugurated in 1994 in the Spanish city, aimed to create a free trade area within 2010 in a context of peace and cooperation. Unfortunately, both the limits of the project and the evolution of the international situation, with the rise of Islamist terrorism, together with some intrinsic limits of the Partnership, led to a partial failure. Looking at a new kind of cooperation, in 2008 the French government launched the project of the Union for the Mediterranean. The outbreak of the Arab Spring in 2011 has temporarily stopped this new experiment of cooperation, confirming, then again, the importance of the Mediterranean theatre in the age of globalization.